1998
DOI: 10.1177/000348949810700411
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superoxide Dismutase in Otitis Media with Effusion

Abstract: The concentration of superoxide dismutase (SOD) in middle ear effusion (MEE) was measured by the electron spin resonance trapping method in order to clarify the role of SOD in otitis media with effusion (OME) in children. The SOD levels in mucoid MEEs were significantly higher than those in serous and purulent MEEs. There was no significant difference in the levels of SOD between neutrophil-dominant MEEs and mononuclear cell-dominant MEEs, and the levels were negatively correlated with the number of neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…Oxygen radicals are also implicated in the pathogenesis of inflammation, and are considered to cause tissue damage by their chemical modification of proteins, carbohydrates, nucleotides, and lipids [15]. Under physiological conditions, ROS are part of normal regulatory circuits and are neutralized by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen radicals are also implicated in the pathogenesis of inflammation, and are considered to cause tissue damage by their chemical modification of proteins, carbohydrates, nucleotides, and lipids [15]. Under physiological conditions, ROS are part of normal regulatory circuits and are neutralized by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…When we reviewed papers regarding infectious diseases and antioxidant status, we realized that the other studies mostly evaluated a few antioxidant enzymes based on only one disease either AOM or acute tonsillitis [15][16][17][18][19]. We hypothesized that a few antioxidant parameters were not enough to judge about all over the antioxidant status.…”
mentioning
confidence: 99%
“…Although in human studies the levels of local antioxidants were found to be increased [9,10], in experimentally induced infections they were found to be decreased [11,12]. Cemek et al [13] explain this contrary with the onset of diseases.…”
Section: Discussionmentioning
confidence: 98%
“…They do so by using a series of oxidants to destroy invading micro-organisms [45]. However, as a side effect, superoxide radicals might damage the membrane of the host cell.…”
Section: Immunologymentioning
confidence: 99%
“…However, as a side effect, superoxide radicals might damage the membrane of the host cell. To protect the host from these oxygen radicals, an important role is played by superoxide dismutase, which is present in higher levels in mucoid than in serous effusions [45].…”
Section: Immunologymentioning
confidence: 99%